Hybrid Model Of Structural Equation Modeling Pls And Rfm (Recency, Frequency And Monetary) Model To Improve Bank Average Balance - Jerry Heikal; Vitto Rialialie; Rivelino, Deva; Ign Agus Supriyono (Pandawan, 2022)
As a business players, entrepreneurs certainly need bank products and supports that provide fast and easy services with wide-spread network in Indonesia. In this study, Structural Equation Model (SEM) identify the transaction that influence the average balance. The objects of the RFM segmentation on the selected transaction is to understand customer segment score and build a marketing strategy for each segment with different levels of loyalty for the Financial result of higher Average Balance. The segmentation results found three driver categories, High Recency, Mid Recency and Low Recency category. High Recency is considered Active customer where campaign category can be cross/up-selling and promotional accordingly with their Frequency and Monetary category. Mid Recency category is considered Risky customer where campaign category can be retention program accordingly with their Frequency and Monetary. Last, Low Recency is considered already Churn customer where campaign category is to conduct reactivation.